Learning to Master the Rules of the Game: A Study of Austrian Diplomats’ Adaptation to the EU - Angers, Kathleen (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2017)
This article analyzes the impact of European Union membership on the practice of diplomacy among new member states. What does it mean, for a diplomat, to move from embodying the nation state to representing a member state? To generate a fine-grained account of the experience of adapting to the EU, I conduct an interview-based study of Austrian diplomats’ adaptation to the EU following their country's accession in 1995. Borrowing from the sociology of Pierre Bourdieu, the interpretation of the data shows the cardinal importance for diplomats of learning to master the rules that have become taken-for-granted in the EU diplomatic field. Learning to deploy effective strategies in a new EU context, I argue, matters significantly more to the successful adaptation of diplomats than being socialized into a new identity does. This empirical finding suggests that the socialization literature in EU studies has not paid enough attention to social practices.